Retrofit minipile system to increase the capacity of existing foundations - ORR, TREVOR L (IHS BRE Press, 2008)
This paper describes a novel underpinning system incorporating Ankerbond and high capacity vertical piles bored through existing concrete foundations. A special cutting head, with three diamond tipped cutters, is used to cut three grooves in the cored holes through the existing concrete foundations. These grooves provide a strong pile head connection to transfer additional load from the existing foundations into the new piles, i.e. the existing foundations are upgraded. The advantages of this system are its ease of installation, its reduced construction time, and its efficiency due to the new vertical piles located closely around the existing columns. The result is that no foundation beams are required and that overall costs are significantly lower than other underpinning solutions. Two case histories are presented which involve the use of the Ankerbond system in conjunction with high capacity retrofitted minipiles. In these case histories, the capacities of the existing foundations were increased to accommodate an additional four storeys on top of existing buildings. Pile compression and tension tests are presented which validate this novel underpinning system and demonstrate its advantages for supporting increased foundation loads.
PUBLISHED
Keywords: Ankerbond; foundations; minipiles; retrofit